Contagious Humanism in Early Nineteenth-Century German-Language Press - Heidi Hakkarainen (United Kingdom, 2022)
Th is article explores the ways the emerging concept of humanism was circulated
and defi ned in early nineteenth-century German-language press.
By analyzing a digitized corpus of German-language newspapers and periodicals
published between 1808 and 1850, this article looks into the ways
the concept of humanism was employed in book reviews, news, political
reports, and feuilleton texts. Newspapers and periodicals had a signifi cant
role in transmitting the concept of humanism from educational debates
into general political language in the 1840s. Furthermore, in an era of growing
social problems and political unrest, humanism became increasingly associated
with moral sentiments. Accordingly, this article suggests that its
new political meanings and emotional underpinnings made humanism culturally
contagious, particularly immediately before and during the 1848/49
revolutions.
KEYWORDS
conceptual history, education, emotions, humanism, politics, press,
1848/49 revolutions